Komunikasi Keluarga dalam Meningkatkan Motivasi Belajar Anak - Zulin Nurchayati (Bidayatuna, 2018)
Education in the family is the basis of children’s education. The process should be supported by family members, especially the parents. Hence, the communication within family motivates and becomes reinforcement in learning process as well as weapon in encountering the problems so that all resolution can be obtained.